Design-driven innovation: exploring enablers and barriers. Issue 5 (2nd August 2019) - De Goey, Heleen; Hilletofth, Per; Eriksson, David
Abstract : Purpose: This study aims to explore the enablers and barriers to design-driven innovation, defined as the innovation of product meanings, in the product-development process. Previous research provides some insights into what enables and hinders design-driven innovation; however a detailed understanding of these factors is missing. Design/methodology/approach: A long-term case study was conducted at a furniture company between 2009 and 2016. Interviews were conducted with respondents within the company, as well as with partners such as retailers and designers. Findings: This paper presents an overview of the identified enablers and barriers. The results demonstrate that enablers and barriers occur in all phases of the product-development process. Second, the connections between enablers and barriers are presented. These are found both within and across different phases, and extend beyond the company's influence. Research limitations/implications: This study demonstrates how the innovation of product meanings is influenced throughout all phases of the product-development process. Therefore, there is a need to go beyond the mere identification of enablers and barriers. More is gained from generating a thorough understanding of the causes and connections of these factors, including the changes over time. Practical implications: This study demonstrates the need for companies to be able to map what enables and hinders design-driven innovation in their product-development process, where a distinction needs to be made between internal and external factors, to enhance value creation. Originality/value: This study presents a rare long-term case study on design-driven innovation. This study provides new knowledge on the enablers and barriers a company faces while adapting its product-development process to accommodate design-driven innovation.